PERANCANGAN DAN PENGEMBANGAN PRESS BAN ELEKTRIK OTOMATIS - Rachmad Hidayat; Mu’alim Mu’alim (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2013)
On tire darning process or in short tire patch a lot of utilize kerosene for goo brew or goo nipping on inner tube that is patched. Now kerosene price crawls to ascend and adequately is hard to be gotten. Method that is utilized in this product development is scheme and Product Development (P3) with aim can give contribution to society in particular effort owner patches tire at territorial one less supply strikes oil. In this scheme there are some that step is acquired shaped product which corresponds to consumer wish amongst those: survey is market, voice of customer, discussion's group and product design determination. Of result gets that data processing tool design patches tire to utilize electricity energy with auto working system which hot control will hang up electricity current what if up to heat dot 112 oC. Compares experimental result tool brew time patch kerosene tire with tool patches memilki's electricity tire time difference 3 minutes. And of return period, tool patches faster electricity tire instead of long time product so alternative is correct more elect tool patches electricity tire with numeral return 0,0028 year and long time product 0,0047 years. Second experimental compare that tool can conclude electric tire patch tool better instead of tool patches to strike oil.